Пошаговое объяснение:
а) (2х - 3)/2 = (1 + х)/4
4*(2x - 3) = 2*(1 + x)
8x - 12 = 2 + 2x
8x - 2x = 2+12
6x = 14
x = 14:6
x = 2 1/3
б) 5х/2 = (19 - 2х)/3
2*(19 - 2x) = 3*5x
38 - 4x = 15x
15x + 4x = 38
19x = 38
x = 38:19
x = 2
в) (2 - х)/5 + 2 = (3+2х)/2
2*(2 - x) + 2*10 = 5*(3 + 2x)
4 - 2x + 20 = 15 + 10x
24 - 2x = 15 + 10x
10x + 2x = 24 - 15
12x = 9
x = 9:12
x = 0,75
г) (х + 2)/8 - х/4 = (3+х)/2
1*(x + 2) - 2*x = 4*(3 + x)
x + 2 - 2x = 12 + 4x
-x + 2 = 12 + 4x
4x + x = 2 - 12
5x = -10
x = -10:5
x = -2
д) (3х + 5)/3 - (х - 4)/6 = х/2
2*(3x + 5) - 1*(x - 4) = 3*x
6x + 10 - x + 4 = 3x
5x + 14 = 3x
5x - 3x = -14
2x = -14
x = -14:2
x = -7
е) (3х + 1)/4 - х/6 = (1 - х)/8
6*(3x + 1) - 4*x = 3*(1 - x)
18x + 6 - 4x = 3 - 3x
14x + 6 = 3 - 3x
14x + 3x = 3 - 6
17x = -3
x = -3 : 17
x = -3/17
а) 7(4f +6)-12f= 28f + 42 - 12f= 16f + 42
б) 8x-(16-2x)∙4= 8x -(64 – 8x)= 8x - 64 + 8x=16x - 64
в) -5p(-x+2y-3k)= - 5px(-x)- 5px 2y - 5px(-3k)= 5px - 10py + 15kp
г) 4c(3a-2)-6a(2c+1)=12ас - 8c - 12ac - 6a= -8c - 6a